MicroRNA-32-5p promotes the proliferation and metastasis of gastric cancer cells - Chao Sun; Lai-gang Huang; Bing Leng; Yanting Guo; Chen Chen; Ruijie Lv; Yan Dong; Tian-tian Gao; De-qing Sun (Scientific Reports)
Abstract Gastric cancer (GC) is a huge threat to global health, there is no effective treatment or just delay the progression of advanced GC until now. Micro-RNAs were reported to participate in the progression of GC. Clonal formation, MTT, caspase-3 activity, sperm DNA fragmentation, flow cytometry assay, cell adhesion, transwell assays were performed to detect the functions of miR-32-5p or anti-miR-32-5p on the growth and metastasis of GC cells. Western blot, qRT-PCR, Co-immunoprecipitation, and luciferase reporter analysis were performed to explore the associated mechanisms. We established mouse tumor xenografts and mouse metastasis models to explore the role of miR-32-5p and anti-miR-32-5p in vivo. We found that miR-32-5p significantly promoting the proliferation and metastasis of GC cells at both in vitro and in vivo levels. The underlying mechanism maybe that miR-32-5p complementary paired with the 3′-UTR of DSC2, and inhibited the expression of DSC2. Furthermore, we found that DSC2 suppressed the transcription of Cyclin B1, and induced G2/M phase arrest through inhibiting the complex of β-catenin/TCF4 in nucleus. We concluded that miR-32-5p negatively regulated the DSC2 expression, might be a potential therapeutic targeting of cancers, most especially in GC.